Improving Teacher Professionalism Through Classroom Action Research to Achieve Better National Education Quality - Syaridawati; Ondeng, Syarifuddin; Mustami, Khalifah (Manunggal Halim Jaya, 2025)
This study aims to explore the role of classroom action research (CAR) in improving teacher professionalism and how such improvements contribute to national education quality, with a particular focus on the Indonesian context. Using a qualitative approach, the study draws on an extensive literature review of peer-reviewed journal articles, policy documents, and empirical case studies to analyze patterns and themes related to teacher development and instructional reform. The findings indicate that CAR is an effective, reflective, and context-sensitive approach that empowers teachers to engage in inquiry-based practice, adapt teaching strategies to student needs, and improve pedagogical competencies. Furthermore, CAR supports collaborative learning cultures and enhances teacher agency, contributing to sustained school improvement and alignment with national education goals. The study concludes that teacher professionalism, when nurtured through structured and supportive CAR initiatives, serves as a foundation for high-quality education. The implications highlight the importance of institutional support, leadership, and mentoring in making CAR a sustainable element of teacher professional development strategies.